The Failure of Communication between Elite in Political Organization - Dadang Rahmat Hidayat, Imam Suhardjo,; Sinaga, Obsatar; Heryanto, Gun Gun (Opción, 2019)
This study aims to analyze managing the conflict in a political party with the perspective of Indonesia’s organizational politic. This research employed in-depth qualitative analysis and interviews with key opinion leaders at the senior level in the political party. The study examines that political communication failure in the organization due to several reasons, including the absence of an imbalance between the composition of the organization, the homogenous community in the organization, and the leader’s personal motives. In conclusion, the imbalance of elements reduces the value of togetherness and causes political communication to be less effective.